CLINICAL AND PATHOLOGICAL PROFILES OF DIABETIC FOOT ULCERS: INSIGHTS FROM A CROSS-SECTIONAL OBSERVATIONAL STUDY - Dr Ajit Singh,Dr Aman Arora,Dr Amandeep Singh Kalra,Dr Nidhi Rao (South Eastern European Journal of Public Health, 2025)
Background: Diabetic foot ulcers (DFUs) represent a significant complication of diabetes mellitus, leading to increased morbidity, mortality, and healthcare costs globally. This study aimed to elucidate the clinical and pathological profiles of DFUs, focusing on ulcer location, microbial culture, the relevance of Wagner’s Classification in predicting amputation necessity, and the impact of Negative Pressure Wound Therapy (NPWT) on hospital stay durations. Methods: We conducted a prospective, cross-sectional observational study at the Department of General Surgery, Command Hospital (Western Command), Chandimandir, over 13 months. Fifty patients presenting with DFUs were enrolled based on defined inclusion and exclusion criteria. Data on socio-demographic characteristics, ulcer specifics, microbial cultures, and treatment outcomes were collected and analyzed. Results: The majority of ulcers were located on the right dorsum (22%), followed by cellulitis (18%) and gangrene (12%). Staphylococcus aureus was the most prevalent pathogen (34%). Higher Wagner’s grades were significantly associated with an increased need for amputation (P < 0.001). NPWT did not significantly reduce hospital stay durations. Post-amputation complications significantly extended hospitalization (P < 0.001). Conclusion: DFUs are characterized by diverse ulcer locations and a significant bacterial load, with Staphylococcus aureus being predominant. Wagner’s Classification is a valuable prognostic tool for assessing the severity of DFUs and the need for amputation. While NPWT is an essential component of DFU management, its effectiveness in reducing hospital stays requires further investigation. Enhanced surgical and post-operative care protocols are crucial in mitigating complications and improving patient outcomes.